The impact of job-related stress on township teachers’ professional well-being: A moderated mediation analysis - Liang, Hongmei; Wang, Weichen; Sun, Yueyang; Wang, Haiying (Frontiers in Psychology, 2022)
This study aimed to explore the relationship between job-related stress and township teachers’ professional well-being. Based on Job Demand-Resource Model, this study examined the mediating role of teachers’ professional identity and the moderating role of perceived organizational support in this relationship. A total of 24,276 township teachers in China responded to the Teacher Stress Scale, the Teachers’ Professional Identity Scale, the Teachers’ Professional Well-Being Structure Questionnaire, and the Perceived Organizational Support Scale. Results showed that: (1) the professional well-being of township teachers differed significantly in terms of school type and demographic characteristics like age and gender; (2) job-related stress negatively predicted township teachers’ professional well-being, with teachers’ professional identity playing a mediating role; (3) the relation between job-related stress and teachers’ professional identity was moderated by perceived organizational support; and (4) in the moderated mediation analysis, job-related stress positively predicted township teachers’ professional well-being. These findings indicated that township teachers’ professional well-being was influenced by both organizational and individual factors, which provided a theoretical basis and intervention pathways for improving township teachers’ professional well-being.